2022
DOI: 10.1371/journal.pone.0272581
|View full text |Cite
|
Sign up to set email alerts
|

Caulerpa chemnitzia in Darwin threatening Galapagos coral reefs

Abstract: Coral reefs are rare in the Galapagos and there is concern that, like in many areas around the world, they may be degrading due to increasing anthropogenic pressure, which can cause changes and reorganizations of structure and function with associated phase shifts. Algae of the genus Caulerpa J.V. Lamouroux, 1809 are known as widespread and persistent marine invaders. They grow rapidly, particularly in disturbed areas where they can opportunistically monopolize substratum and compete with native species, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Fast-growing algae can outcompete corals, particularly in already compromised areas; C. chemnitzia is thus a threat to Darwin Island's Wellington Reef (CDF, 2022). Recent work by Keith et al (2022) reported that C. chemnitzia populations grow and contract in response to climate change, calling for an early detection rapid response system to monitor marine invasive species.…”
Section: Invasive Marine Speciesmentioning
confidence: 99%
“…Fast-growing algae can outcompete corals, particularly in already compromised areas; C. chemnitzia is thus a threat to Darwin Island's Wellington Reef (CDF, 2022). Recent work by Keith et al (2022) reported that C. chemnitzia populations grow and contract in response to climate change, calling for an early detection rapid response system to monitor marine invasive species.…”
Section: Invasive Marine Speciesmentioning
confidence: 99%